Recobrimentos de EPIs com nanopartículas de óxido de ferro: uma proposta virucida - Constantino, Jamilly Salustiano Ferreira (2024)
This study described the development and characterization of hybrid coatings incorporating iron oxide nanoparticles on cotton and polypropylene surfaces. The goal was to produce effective preventive materials against highly transmissible viral diseases, such as the coronavirus, which can survive on surfaces for long periods. For this purpose, iron oxide nanoparticles were synthesized, and transmission electron microscopy images revealed their crystalline structure. X-ray diffraction confirmed the predominance of magnetite in the nanoparticles. Consequently, hybrid coating systems with different biopolymers and iron oxide nanoparticles were produced and evaluated for their virucidal activity against the coronavirus and dermal toxicity. Among the coatings studied on cotton fabric, the one based on N-succinyl chitosan showed the lowest release of iron ions after 24 hours compared to other hybrid coatings. Additionally, this hybrid coating achieved 99% virucidal activity within 5 minutes of contact, and all coatings exhibited 99.9999% viral inactivation capacity within 24 hours. Regarding acute dermal toxicity, the evaluation was conducted according to OECD guideline 402, demonstrating safety for topical use. Based on these results, the same hybrid coating was applied to polypropylene surfaces previously modified with cold vacuum plasma to improve coating adhesion. Additionally, iron oxide nanoparticles were combined with (3-aminopropyl)triethoxysilane to form robust mucoadhesive films. The results indicated that these hybrid coatings significantly improved the virucidal properties of polypropylene surfaces, effectively inactivating the Coronaviridae MHV-3 strain in just five minutes of exposure. Furthermore, the coatings demonstrated good breathability, according to European standards, and cytotoxicity tests confirmed biocompatibility with fibroblasts and keratinocytes, highlighting their potential for safe application in personal protective equipment, such as face masks.